Novel Role for Netrins in Regulating Epithelial Behavior during Lung Branching Morphogenesis - Liu, Yuru (2004)
The development of many organs, including the lung, depends upon a process known as branching morphogenesis, in which a simple epithelial bud gives rise to a complex tree-like system of tubes specialized for the transport of gas or fluids. Previous studies on lung development have highlighted a role for fibroblast growth factors (FGFs), made by the mesodermal cells, in promoting the proliferation, budding, and chemotaxis of the epithelial endoderm [1–3]. Here, by using a three-dimensional culture system, we provide evidence for a novel role for Netrins, best known as axonal guidance molecules [4, 5], in modulating the morphogenetic response of lung endoderm to exogenous FGFs. This effect involves inhibition of localized changes in cell shape and phosphorylation of the intracellular mitogen-activated protein kinase(s) (ERK1/2, for extracellular signal-regulated kinase-1 and -2), elicited by exogenous FGFs. The temporal and spatial expression of netrin 1, netrin 4, and Unc5b genes and the localization of Netrin-4 protein in vivo suggest a model in which Netrins in the basal lamina locally modulate and fine-tune the outgrowth and shape of emergent epithelial buds.